PENGARUH MODAL, TINGKAT PENDIDIKAN, DAN LAMA USAHA TERHADAP PENDAPATAN PEDAGANG DI PASAR INDUK KECAMATAN MAJENANG - Hikmawati, Naeni; Jayanti, Esih; Z, Zamroni (JURNAL EKONOMI, 2025)
This study aims to examine the effect of Capital (X1), Education Level (X2), and Length of Business (X3) on Trader Income (Y) at the Central Market in Majenang District. Data was collected by distributing questionnaires to 120 traders at the Central Market in Majenang District. The sampling technique in this study used accidental sampling. Data analysis techniques used include validity test, reliability test, MSI (Method of Successive Interval) test, classic assumption test includes linearity test, normality test, multicollinearity test, and heteroscedasticity test, multiple linear regression analysis, hypothesis testing includes t-test and test F, analysis of the coefficient of determination (R²). The analysis results show that capital has a significant effect on the income of traders in the Main Market, Majenang District. The two levels of education significantly affect the income of traders in the Main Market, Majenang District. The three lengths of business have a significant effect on the income of traders in the Main Market, Majenang District. The four capitals, level of education, and length of business simultaneously significantly affect the income of traders at the Central Market in Majenang District.